2014
DOI: 10.4097/kjae.2014.67.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect on thermoregulatory responses in patients undergoing a tympanoplasty in accordance to the anesthetic techniques during PEEP: a comparison between inhalation anesthesia with desflurane and TIVA

Abstract: BackgroundIt has been known that positive end-expiratory pressure (PEEP) increases the vasoconstriction threshold by baroreceptor unloading. We compared the effect on the thermoregulatory responses according to anesthetic techniques between an inhalation anesthesia with desflurane and a total intravenous anesthesia (TIVA) with propofol and reminfentanil when PEEP was applied in patients undergoing tympanoplasty.MethodsForty-six patients with a scheduled tympanoplasty were enrolled and the patients were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 17 publications
2
11
1
Order By: Relevance
“…Numerous previous reports have indicated that peripheral vasoconstriction by PEEP-induced baroreceptor unloading effectively prevents intraoperative hypothermia. 10 , 11 , 13 , 14 Although the present study revealed the beneficial effect of PEEP on thermoregulatory reactions (a high threshold and rapid onset of peripheral vasoconstriction), there were no significant differences in the core temperature changes over time between the two groups. This discrepancy regarding the effects of PEEP on intraoperative core temperature may be explained in part by the cold environment and prone positioning in our experimental setting.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Numerous previous reports have indicated that peripheral vasoconstriction by PEEP-induced baroreceptor unloading effectively prevents intraoperative hypothermia. 10 , 11 , 13 , 14 Although the present study revealed the beneficial effect of PEEP on thermoregulatory reactions (a high threshold and rapid onset of peripheral vasoconstriction), there were no significant differences in the core temperature changes over time between the two groups. This discrepancy regarding the effects of PEEP on intraoperative core temperature may be explained in part by the cold environment and prone positioning in our experimental setting.…”
Section: Discussioncontrasting
confidence: 61%
“…Thermoregulatory vasoconstriction was evaluated with the same method used in several previous studies. 11 , 13 , 14 The difference in skin temperature between the forearm and fingertip was also calculated. A forearm–fingertip skin temperature difference of <0°C was defined as peripheral vasodilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, cervical sympathetic involvement from IBPB might cause vasodilation of the upper extremity, head, and neck of the ipsilateral side of the block, affecting temperature measurement on the ipsilateral side of block before induction of anesthesia and in the PACU. A skin temperature thermometer on the upper extremity might be helpful to determine whether peripheral vasodilation or constriction developed [ 19 ]. Second, additional rocuronium was administered for the prevention of any patient movement during arthroscopic surgery with the appearance of clefts in the capnogram.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a forced-air warming device should have been applied to patients whenever body temperatures fell below 36.5℃ during the operation and below 36℃ in the PACU according to the National Institute for Health and Care Excellence (NICE) clinical guideline 65. This study adopted a lower temperature than that suggested in the NICE guideline before active warming measures, referring to other studies [ 2 3 19 21 ].…”
Section: Discussionmentioning
confidence: 99%